Carving The Future of Nature Ecotourism in Indonesia: Case of Taman Wisata Alam Telogo Warno Telogo Pengilon - Tri Satyatama; Lies Rahayu Wijayanti Faida; Ris Hadi Purwanto; Chafid Fandeli (Jurnal Manajemen Hutan Tropika, 2020)
Indonesia has potential ecotourism spots that are need to be utilized as well as to increase the value of forest benefits from the aspect of environmental services while maintaining the function of the area. However, there are contraints in managing natural tourism in conservation areas according to the concept of sustainable tourism. This study focuses on the performance of sustainable nature tourism management applied in Taman Wisata Alam Telogo Warno Telogo Pengilon (TWA TWTP) that is carried out in the form of a partnership between the Balai Konservasi Sumber Daya Alam Jawa Tengah (Central Java Natural Resources Conservation Office; BKSDA) and PT. Alam Indah Bonbin Lestari (AIBBL) as the holder of Ijin Usaha Penyediaan Sarana Wisata Alam (Business License for the Provision of Nature Tourism Facilities; IUPSWA). The results show positive improvement in the management of TWA TWTP. However, several issues that require immediate improvement still remain. In general, all of the aspects are categorized in to four scopes: (1) management of effective sustainable tourism destination, (2) the optimization of economic benefits for local communities, (3) the optimization of cultural preservation for the communities and visitors, and (4) environmental conservation.